Mayan Tales from Chiapas, Mexico - Laughlin, Robert M. (Book collections on Project MUSE., 2014)
Presented here in English, Tzotzil, and Spanish are forty-two stories told to Robert Laughlin in Tzotzil by the only speaker of Tzotzil left in the village of San Felipe Ecatepec in Chiapas, Mexico. The stories range from mythological sacred stories to historical accounts of life in the twentieth century.